2022
DOI: 10.1371/journal.pone.0265177
|View full text |Cite
|
Sign up to set email alerts
|

Continuous cash dividends, ownership structure and firm value: Evidence from Chinese A-share market

Abstract: This paper examines the relation between continuous cash dividends, ownership structure and firm value across a sample of 1503 firms listed on Chinese A-share market from 2009 to 2017. The empirical results reveal (1) the positive effect of continuous cash dividends on firm value and that (2) values of both state-owned enterprises controlled by central government (SOECGs) and state-owned enterprises controlled by local governments (SOELGs) that distribute continuous cash dividends increase more with ownership … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
1
1
0
Order By: Relevance
“…It can be concluded that the dividend cannot be used as a tool to assess price to book value in manufacturing companies. This finding is in line with Sutomo & Budiharjo (2019) who state that dividend policy is not significant to Company value, and according to Qi et al (2022) who state that dividends are significant to company value. This finding is in line with the agency theory that dividing income into dividends and retained earnings can increase agency costs.…”
Section: Dividend On Company Valuesupporting
confidence: 86%
“…It can be concluded that the dividend cannot be used as a tool to assess price to book value in manufacturing companies. This finding is in line with Sutomo & Budiharjo (2019) who state that dividend policy is not significant to Company value, and according to Qi et al (2022) who state that dividends are significant to company value. This finding is in line with the agency theory that dividing income into dividends and retained earnings can increase agency costs.…”
Section: Dividend On Company Valuesupporting
confidence: 86%
“…With the development of social economy, traditional ownership and equity are no longer seen as the same concept. The organizational form of enterprises has been separated from ownership and operation through continuous improvement and the operational risks borne by shareholders have been dispersed to stakeholders, such as managers, creditors and employees [23]. As a result, ownership includes equity and other stakeholders' rights and the management goal of maximizing shareholders' interests becomes maximizing stakeholders' rights and interests [24].…”
Section: Introductionmentioning
confidence: 99%